Calcium hydroxide coating for orthopedic implants: evaluation of osseointegrative and antibacterial properties in vivo - von Hertzberg-Boelch, Sebastian Philipp; Ewald, Andrea; Meininger, Markus; Ludwig, Julia; Vogt, Fabian; Groll, Jürgen; Rudert, Maximilian (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeWe evaluated the osseointegrative and antibacterial properties of calcium hydroxide-coated titanium implants in this study and compared them to uncoated implants in a rabbit model.MethodsCoated and uncoated implants were implanted into both femora of 19 New Zealand white rabbits. After retrieval, the osseointegrative properties were compared via quantification of bone–implant contact and proportion of unmineralized bone around the implant; further, the antibacterial properties were assessed using a Staphylococcus aureus infection model. The bacterial burden on and around the implants as well as the immunoreactions of the hosts were quantified using the neutrophil percentage in the tissue and effusion from the affected knees.ResultsThe bone–implant contact was significantly higher (p < 0.000) around the coated implant, whereas the proportion of osteoids was significantly higher around the uncoated implant (p = 0.001). The antibacterial effects of the coated implants were not significant. However, bacterial presence on the implant was observed in only 20% of the coated but 75% of the uncoated implants. The overall infection score indicated lower infection activities at joints with coated implants.ConclusionCalcium hydroxide is a promising coating for titanium implants. Our animal study demonstrates the improved osseointegrative properties and evidences the topical antibacterial effects of coated implants.